EKSPLORASI PERAN TIKTOK SEBAGAI MEDIA EKSPRESI SENI PERTUNJUKAN REMAJA: STUDI PUSTAKA (Jurnal Sitakara, 2026)
This research aims to explore the role of TikTok as a medium for youth performing arts expression in the digital era. The problem is focused on the emerging forms of artistic expression found on TikTok and how the platform shapes the understanding of art and impacts performing arts education. In order to approach this problem, theoretical references from digital media studies, self-expression, and arts education were used, with a library research method. The data were collected through a review and selection of relevant academic literature published within the last ten years and analyzed using descriptive-qualitative techniques. The findings indicate that TikTok has become a dominant space for teenagers to present performing arts such as traditional and contemporary dance, short dramas, lip-sync performances, and visual storytelling. Teenagers utilize TikTok’s creative features to express themselves artistically, although their understanding of aesthetics tends to be instant and focused on visual appeal. This study concludes that TikTok holds potential as a contextual and participatory medium for performing arts learning, yet it needs to be critically and purposefully integrated into arts education to maintain cultural, aesthetic, and educational values.Kata Kunci: TikTok; seni pertunjukan; remaja; ekspresi digital; pendidikan seni.